Study of Marine Fishing Grounds Based on the Content of Chlorophyll-a And Sea Surface Temperature Via Satellite Imagery of Aqua MODIS of Marine Areas of Rokan Hilir Regency - Sunarti '; Joko Samiaji; Mubarak ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The study was conducted in October-December 2013. The area of studywas in Rokan Hilir coastal waters, while data analysis was done in the PhysicalOceanography Laboratory, University of Riau, Pekanbaru. The method used wassurvey method with the materials were obtained from the imagenary satellite byusing Aqua MODIS level 1b. The analysis was supported by using software ofEnvi 4.5 and Arcgis 10.The result showed the chlorophyl-a concentration in Rokan Hilir regencywaters varied for each month. In October the value of chlorophyl-a ranged from0.211-1.736 mg/m³, in November the concentration ranged from 0.217-1.731mg/m³, whereas in December the value ranged from 0,286-1,914 mg/m³. The seasurface temperature for each month showed as follows: in Oktober 25°c to 30°c,in November 26°c to 30°c, in December 29°c to 32°c, respectively. The visualanalysis showed that the most potential fishing grounds were found along thecoastal areas of Sinaboi, Sei Nyamuk, and Pulau Halang.Keywords: Fishing Grounds, Chlorophyll-a, Sea Surface Temperature AquaFashionable, And Marine Areas Rokan Hilir.